Synthesis and biological properties of 7-(2-hydroxy-3-m-ethylphenoxypropyl-1-)theophilline derivatives - D. G. Ivanchenko (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Various origin antibiotics and many other chemotherapeutic agents, which are based on the heterocyclic compound, found wide application in the treatment of infectious diseases. Purine derivatives have long been used in medical practice as antiviral agents (acyclovir, gancyclovir, etc.), and further research to find new antimicrobial and antiviral agents in the row of purine derivatives are justified and perspective. The aim of this paper is to elaborate simple laboratory methods of 7,8-disubstituted theophylline synthesis, unspecified in scientific papers earlier, and to study their physical and chemical properties. The melting point has been determined by open capillary method on the device PTP (M). Elemental analysis has been performed on the device Elementar Vario L cube. NMR spectra have been taken using spectrometer Bruker SF-400. For the initial screening study of the newly-synthesized substances benchmark testing-cultures of both gram-positive and gram-negative bacteria have been used, which belong to clinically significant groups of infections agents which are differing by their morpho-physiological properties. Heating of 8-bromotheophilline with m-ethylphenoxymethyloxyrane in propanol-1 environment results in formation of 8-bromo-7-(2-hydroxy-3-m-ethylphenoxypropyl-1-)theophylline. Its reactions with primary and secondary amines proceed at boiling in aqueous dioxane environment to form the corresponding 8-aminoderivatives. The heating of initial syntone with 2-ethylpiperidine leads to the formation of oxazoline xanthine. By applying such computer programs as ALOGPS, DRAGON, GUSAR and ACD/Percepta Platform was established viability of further biological and toxicological in vitro and in vivo research. Simple laboratory method has been elaborated to synthesize 8-bromo-7-(2-hydroxy-3-m-ethylphenoxypropyl-1-)theophylline, which is initial compound for further synthesis of various theophylline N-, O-, S-substituted. Reactions of 8-bromo-7-(2-hydroxy-3-m-ethylphenoxypropyl-1-)theophylline with primary and secondary amines have been investigated. As a result 8-aminosubstituted of 7-(2-hydroxy-3-m-ethylphenoxypropyl-1-)theophylline and 6,8-dimethyl-2-m-ethylphenoxymethyl-2,3-dihydro-1,3-oxazolo[2,3-f]theophylline have been synthesized. NMR-spectral characteristics of new synthesized compounds have been studied. Molecular and pharmacological descriptors (LogP, TPSA, A) to forecast properties of the obtained substances have been calculated, in addition to acute toxicity index. The perspective of the obtained substances using as antistaphylococcal and antifungal agents has been shown.